Along-rift propagation of Pleistocene-Holocene faults from a central volcano. (December 2020) - Tibaldi, A.; Corti, N.; Bonali, F.L.; Pasquaré Mariotto, F.; Russo, E.
Abstract: The mechanisms of rift propagation are still not fully understood, especially at mid-oceanic ridges, owing to the inherent difficulty in collecting submarine data. Here, we investigate the fault slip profiles of the 60-km-long Theistareykir rift (northern Iceland) that may suggest the direction of along-axis rift propagation. This is one of the few places on Earth where rifting processes and mid-oceanic ridge formation can be studied directly. Moreover, this rift hosts an active central volcano, and this enables to fully understand the relations between rift propagation and magma systems. We reconstructed the slip profiles of all the 281 main Pleistocene-Holocene faults that compose this N-S rift, by merging measurements performed in the field, collected by Unmanned Aerial Vehicle surveys, and derived from Digital Surface Models. Results indicate that north of the volcano, 75% of the asymmetric faults propagated northward; the value increases to 82% if the cumulated fault length is considered. South of the volcano, 47% of the asymmetric faults propagated southward, 54% if the cumulated fault length is considered. These data point to a dominant mechanism of along-axis propagation of the rift outward from the volcano, suggesting a genetic link with the underlying magma chamber. Two possible processes are suggested, which can also occur in combination: i) faults develop following lateral dyke propagation outward from the magma chamber, and ii) faults nucleate near the volcano as a consequence of the different crustal rock rheology produced by a higher heat flux. The rift architecture is complicated by the presence of tectonic zones with different dominant fault dips, separated by transversal accommodation zones. The latter also play the role of barriers guiding local fault propagation. Highlights: We reconstructed the slip profiles of all the faults composing the Theistareykir rift. Slip profile tapering suggests rift propagation outward from a central volcano. Faults can develop following dyke propagation outward from the magma chamber. Faults may nucleate near the magma chamber due to different crustal rock rheology. Rift-transversal accommodation zones may locally act as barriers to fault propagation.